2009 IEEE Conference on Electrical Insulation and Dielectric Phenomena 2009
DOI: 10.1109/ceidp.2009.5377858
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical treeing in XLPE/silica nanocomposites

Abstract: Ashcraft-type samples have been used to grow vented water trees in crosslinked polyethylene and crosslinked polyethylene based nanocomposites with 5 wt% and 12.5 wt% functionalized silica. Tree growths are reported at a range of stresses by sectioning the samples destructively. A nondestructive method is also introduced which allows visualization of electrochemical trees without sectioning. Nanocomposites are found to have higher resistance to water tree growth and this trend becomes clear with larger loading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Over the last years, insulations based on various PE-based nanocomposites were manufactured. For the experimental work, two types of models are mainly used, ( i ) the uniform field models [246,259] and ( ii ) divergent field models [246,260,261]. The electrolyte solutions are commonly prepared with NaCl but also other salts such as AgNO 3 , CuSO 4 , Fe 2 O 3 and so forth, are used; their concentrations being in the range of 0.01 to 10 M [246].…”
Section: Water Treeing In Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, insulations based on various PE-based nanocomposites were manufactured. For the experimental work, two types of models are mainly used, ( i ) the uniform field models [246,259] and ( ii ) divergent field models [246,260,261]. The electrolyte solutions are commonly prepared with NaCl but also other salts such as AgNO 3 , CuSO 4 , Fe 2 O 3 and so forth, are used; their concentrations being in the range of 0.01 to 10 M [246].…”
Section: Water Treeing In Nanocompositesmentioning
confidence: 99%
“…Series of research studies were performed on samples based on LDPE and XLPE with different types of inorganic nanofillers [240,260,262,263,264,265]. Huang et al studied the effect of nano-SiO 2 particles on the water trees growth in LDPE [262].…”
Section: Water Treeing In Nanocompositesmentioning
confidence: 99%
“…The concentration of by-products depends on the temperature used for crosslinking. Hence, researchers have adopted degassing and annealing processes to remove the by-products [88][89][90][91][92]. Additionally degassing reduces the space charge accumulation [88].…”
Section: Other Dielectric Propertiesmentioning
confidence: 99%
“…Different types of particles have been used as fillers in the epoxy-based polymer composite. These include silica, carbon nanotubes, oxides of metals, graphene oxide, barium ferrite and clay [6][7][8][9][10][11]. Earlier work revealed that polymer micro-and nanocomposite materials have quite different dielectric behaviour.…”
Section: Introductionmentioning
confidence: 99%